1997
DOI: 10.1016/s0735-1097(97)00058-2
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Septal Defect in Adults: Cardiopulmonary Exercise Capacity Before and 4 Months and 10 Years After Defect Closure

Abstract: Although preoperative cardiopulmonary capacity in adult patients with nonrestrictive ASD was significantly decreased, some improvement was seen at 4 months postoperatively, with complete restitution to normal at 10 years after shunt closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
4
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 19 publications
7
32
4
2
Order By: Relevance
“…Improvement in exercise capacity occurred early after the procedure. This is in contrast to the study by Helber et al, 21 who reported no change in VO 2max 4 months after surgery but a normalization in the predicted VO 2max at 10 years; the authors commented that this delay could be explained by the trauma of operation, a situation avoided in our population by the use of a percutaneous device. Because there was no mention of the functional class in the 22 patients who completed the 10-year evaluation, it could not be inferred, however, that the benefit in exercise capacity was present in asymptomatic and mildly symptomatic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Improvement in exercise capacity occurred early after the procedure. This is in contrast to the study by Helber et al, 21 who reported no change in VO 2max 4 months after surgery but a normalization in the predicted VO 2max at 10 years; the authors commented that this delay could be explained by the trauma of operation, a situation avoided in our population by the use of a percutaneous device. Because there was no mention of the functional class in the 22 patients who completed the 10-year evaluation, it could not be inferred, however, that the benefit in exercise capacity was present in asymptomatic and mildly symptomatic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Functional improvement of previously asymptomatic patients has been reported after secundum ASD closure. 15 Lack of preoperative symptoms is not a contraindication to the current practice of secundum ASD repair and should not be a contraindication for repair of SVASD, even in adults.…”
Section: Postoperative Symptoms and Long-term Follow-upmentioning
confidence: 99%
“…In those patients with large left-to-right shunts, exercise is often self-limited owing to decreased cardiopulmonary function. 273 Symptomatic supraventricular or ventricular arrhythmias may also compromise exercise capacity and impose limitations on engagement in competitive sports. Patients with significant PAH (peak systolic pulmonary artery pressure greater than 40 mm Hg) should limit their activity to low-intensity sports.…”
Section: Activitymentioning
confidence: 99%